Desenvolvimento de um aplicativo de troca de mensagens entre dispositivos celulares de maneira totalmente offline - Oliveira, Marcos Laelber Jacó. (2021)
Communication between people via mobile devices is very common nowadays. However, there are still some places or situations where communication is not possible due to lack of Internet. Nonetheless, offline communication networks can be formed through ad hoc structures, MANET, and Nearby Connections. Although, these structures present some challenges, such as the need for equipment to help send messages or for the receiver to be within the transmission radius of the sender. Considering the low range of these forms of communication, an application was created to exchange offline messages in a way that the receiver does not necessarily need to be within the transmission radius of the sender. For this, exploratory research was carried out in order to find protocols, network structure, APIs and routing algorithms that could help solve the problem. In addition, a comparison between the identified protocols was performed. The results showed that APINearby Connections provides services for connecting and exchanging data offline between devices. The application was developed with the help of Nearby Connections and tested in a real environment. An application was obtained that was able to exchange messages in an offline manner that allows hopping between devices. We conclude that the application is a good alternative for environments that require offline communication. However, studies can be conducted in order to ensure greater security.